2020
DOI: 10.1183/16000617.0184-2019
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in advanced diagnostic bronchoscopy

Abstract: The field of bronchoscopy is advancing rapidly. Minimally invasive diagnostic approaches are replacing more aggressive surgical ones for the diagnosis and staging of lung cancer. Evolving diagnostic modalities allow early detection and serve as an adjunct to early treatment, ideally influencing patient outcomes. In this review, we will elaborate on recent bronchoscopic developments as well as some promising investigational tools and approaches in development. We aim to offer a concise overview of the significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In the past decades, bronchoscopy has undergone a great development and extensive use, and the types of procedures have changed and become more complex and sophisticated [1] . Because of the noncontemporaneous nature of previous studies, it is necessary to reanalyze the incidence and type of complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, bronchoscopy has undergone a great development and extensive use, and the types of procedures have changed and become more complex and sophisticated [1] . Because of the noncontemporaneous nature of previous studies, it is necessary to reanalyze the incidence and type of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported complication rates up to 1.44% [ 30 34 ]. Substantial evidence also suggests that CEBUS-TBNA exhibits high diagnostic yield and low complication rates in diagnosing benign diseases [ 35 , 36 ]. These CEBUS-TBNA findings align with the diagnostic yield of 92% and complication rate of 4% reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in addition to obtaining diagnostic tissue specimens using biopsy forceps, bronchoscopy with brushing or bronchoalveolar lavage can also contribute to the diagnosis with remarkable specificity 150 . Among the newer bronchoscopy‐based technologies, 151 endobronchial ultrasound‐guided transbronchial needle aspiration is preferably used for tumors with peribronchial localization and for enlarged mediastinal or hilar lymph nodes 146,152 . Another approach for mediastinal staging is mediastinoscopy (Figure 5B), which is performed under general anesthesia.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%